2021
DOI: 10.1101/2021.03.29.21254532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive modelling of COVID-19 New Confirmed Cases in Algeria using Artificial Neural Network

Abstract: This study investigates the potential of a simple artificial neural network for the prediction of COVID-19 New Confirmed Cases in Algeria (CNCC). Four different ANN models were built (GRNN, RBFNN, ELM, and MLP). The performance of the predictive models is evaluated based on four numerical parameters, namely root mean squared error (RMSE), mean absolute error (MAE), Nash-Sutcliffe efficiency (NSE), and Pearson correlation coefficient (R). Taylor diagram was also used to examine the similarities and differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[9] aimed to predict the prevalence of Covid-19 in Nigeria using a linear regression model. Djeddou et al [10] used four different artificial neural network models to model newly confirmed cases in Algeria. Achterberg et.…”
Section: Introductionmentioning
confidence: 99%
“…[9] aimed to predict the prevalence of Covid-19 in Nigeria using a linear regression model. Djeddou et al [10] used four different artificial neural network models to model newly confirmed cases in Algeria. Achterberg et.…”
Section: Introductionmentioning
confidence: 99%